Copy number variations in Saudi family with intellectual disability and epilepsy. (October 2016) - Naseer, Muhammad; Chaudhary, Adeel; Rasool, Mahmood; Kalamegam, Gauthaman; Ashgan, Fai; Assidi, Mourad; Ahmed, Farid; Ansari, Shakeel; Zaidi, Syed; Jan, Mohammed; Al-Qahtani, Mohammad
Abstract Background Epilepsy is genetically complex but common brain disorder of the world affecting millions of people with almost of all age groups. Novel Copy number variations (CNVs) are considered as important reason for the numerous neurodevelopmental disorders along with intellectual disability and epilepsy. DNA array based studies contribute to explain a more severe clinical presentation of the disease but interoperation of many detected CNVs are still challenging. Results In order to study novel CNVs with epilepsy related genes in Saudi family with six affected and two normal individuals with several forms of epileptic seizures, intellectual disability (ID), and minor dysmorphism, we performed the high density whole genome Agilent sure print G3 Hmn CGH 2x 400 K array-CGH chips analysis. Our results showedde novo deletions, duplications and deletion plus duplication on differential chromosomal regions in the affected individuals that were not shown in the normal fathe and normal kids by using Agilent CytoGenomics 3.0.6.6 softwear. Copy number gain were observed in the chromosome 1, 16 and 22 withLCE3C, HPR, GSTT2, GSTTP2, DDT andDDTL genes respectively whereas the deletions observed in the chromosomal regions 8p23-p21 (4303127–4337759) and the potential gene in this region isCSMD1 (OMIM: 612279). Moreover, the array CGH results deletions and duplication were also validated by using primer design of deleted regions utilizing the flanked SNPs using simple PCR and also by using quantitative real time PCR. Conclusions We found some of thede novo deletions and duplication in our study in Saudi family with intellectual disability and epilepsy. Our results suggest that array-CGH should be used as a first line of genetic test for epilepsy except there is a strong indication for a monogenic syndrome. The advanced high through put array-CGH technique used in this study aim to collect the data base and to identify new mechanisms describing epileptic disorder, may help to improve the clinical management of individual cases in decreasing the burden of epilepsy in Saudi Arabia.